Qualitative comparative analysis of success factors of rural property social management plans in Colombia in the formulation and implementation phases (2018-2021) - Rodríguez Moreno, Ana Catalina; Hernández, Alejandro; Martínez Cortés, Luis Francisco (Cuadernos de Administración, 2023)
As a result of the signing of the Peace Agreement in 2016 and point one on Comprehensive Rural Reform, the Colombian government assumed the task of implementing a policy for the Social Use of Rural Property focused on extending to the rural population, legalization mechanisms in terms of access to land and formalization of rural property. Because of the development of this task, for the period 2018-2021, the authors present the main aspects of Qualitative Comparative Analysis (QCA) on the formulation and implementation of Rural Property Social Management Plans (POSPRs –Spanish acronym) as public policy instruments, in the framework of nine agreements concluded between the National Land Agency and its partners. The main objective is to find conditioning factors for successfully formulating and implementing the POSPR methodological route. To this end, the authors systematically identify and analyze variables present in the relationship between goals and results of an action plan and organize them as configurations of a plausibly causal nature. The study discusses concepts of rural development public policy. Among the empirical results, methodological development and participation of the community, together with access to operational inputs in the face of a favorable territorial context, are elements shaping the success of the POSPRs during 2018-2021. By using relatively novel analysis techniques and presenting details of their process, the study contributes to their dissemination in public administration research.